Catalytic pyrolysis of holocellulose followed by integrated aldol condensation and hydrogenation to produce aviation fuel. (15th July 2022) - Shao, Shanshan; Ye, Zian; Liu, Chengyue; Hu, Xinggang; Sun, Jiayuan; Li, Xiaohua; Zhang, Huiyan; Xiao, Rui
Graphical abstract: Highlights: The carbonyls from CFP of holocellulose as platform compounds were prepared. The carbonylation of pyrolysis gas from bagasse-derived holocellulose was more favorable. 400 °C was optimized for the production of hydrocarbons from bagasse-derived bio-oil. Mass yield of aviation fuel of 14.23% can be obtained from the original biomass. Theoretical and economic analysis was provided for the production of aviation fuel. Abstract: The carbonyl platform compound from the catalytic pyrolysis of holocellulose was employed for the integrated aldol condensation and hydrogenation to produce hydrocarbons in the range of jet fuel. By the carbonylation of the pyrolysis vapor from holocellulose prepared from rape straw, bagasse and poplar (RS-Holo, BG-Holo and PL-Holo), it was revealed that BG-Holo rich in cellulose as the raw material presented the most production of carbonyl compounds including aldehydes and ketones. The optimal temperature for carbonylation of pyrolysis vapor from holocellulose was determined to be 400 °C, with the maximized carbon yield of carbonyls reaching 46.11%, which was boosted to the summit of 53.59% with more addition of ZrO2 catalyst. The integrated aldol condensation and hydrogenation were carried out using the catalytic pyrolysis bio-oil as the reactant over Ni/Mg-Al-O/AC bifunctional catalyst, with the highest carbon yield of hydrocarbons reaching 78.11%. The production mechanism of the final targeted alkanes was speculated, and it was discovered that ketones and aldehydes with short carbon chains are more prone to secondary condensation than those with long carbon chains, resulting in high-energy–density aviation fuel. Furthermore, the heating value of final oil was calculated based on an empirical formula, which was comparable to that of Jet A, meeting the standard of ASTM7566. The final oil's distillation range distribution was simulated, and most of it fell in the range of aviation fuel. In this study, catalytic fast pyrolysis of holocellulose followed by integrated aldol condensation and hydrogenation was proved to be a promising way for producing aviation fuel.